Chapter I Castelbarco nel Trecento e nel Quattrocento: apogeo e disfacimento di una signoria di valle - LANDI, Walter (Reti Medievali E-Book, 2023)
The Castelbarco family, settled since the 12th century in the 'road area' of the Val Lagarina (between Verona and Trento), the main route between Italy and northern Europe, reached its greatest authority at the beginning of the 14th century. This was followed by a splitting of the Castelbarco seigniory and a growing influence of the German Empire.